Bacillus cereus (EG-Q3) in the Gut of Ectropis grisescens Contributes to Host Response to Starvation Conditions - Li, Xiayu; Zhang, Yong; Zhou, Linlin; Gao, Tian; Zhao, Yu; Liu, Song; Su, Qingqing; Wei, Chaoling; Yang, Yunqiu; Long, Yanhua (Frontiers in Microbiology, 2022)
The gut bacteria of insects play an important role in their nutrition, maintenance, and ecological adaption. Ectropis grisescens is the most important leaf-feeding pest in tea gardens in China. In order to explore whether E. grisescens adaptation under starvation stress is related to its gut bacteria, we used a culture-independent method to compare the composition and diversity of their gut bacteria under starvation treatment. The results revealed no significant changes in core gut bacteria composition and diversity within 24 h of starvation. However, non-core gut bacterial Bacillus increased significantly under starvation conditions. B. cereus strain EG-Q3 isolated from the gut of E. grisescens in carbon source-selected medium showed the ability to degrade fat bodies from E. grisescens in vitro and in vivo. Moreover, the fat-lowering ratio of E. grisescens fed with B. cereus strain EG-Q3 (6.76 ± 1.281%) was significantly higher than that of the control group (3.96 ± 0.801%, t = 4.15, df = 8, p < 0.01) after starvation for 4 h. These findings suggest that non-core gut bacterial B. cereus strain EG-Q3 contributes to host adaptation to starvation. Together, this research provides evidence that E. grisescens may benefit from non-core gut bacteria under starvation conditions.